Exfoliated conjugated porous polymer nanosheets for highly efficient photocatalytic hydrogen evolution. Issue 9 (8th February 2021) - Cheng, Jing-Zhao; Tan, Zhi-Rong; Xing, Yu-Qin; Shen, Zhao-Qi; Zhang, Yu-Jie; Liu, Li-Lin; Yang, Kai; Chen, Long; Liu, Shi-Yong
Abstract : A common strategy is developed to exfoliate bulk CPPs into nanosheets for highly efficient PHP performance. Abstract : In this contribution, we developed a simple, scalable, and universal strategy to exfoliate conjugated porous polymers (CPPs) into 2D nanosheets. A series of pyrenyl (Py )-, benzene (B )-, thienyl (T )-, thieno[3, 2- b ]thiophene (Tt )- and dithieno[3, 2- b :2′, 3′- d ]thiophene (Ttt )-based CPPs were facilely exfoliated into 2D ultrathin sheets with a thickness of 5–18 nm in reasonable yields of 6–20% upon sonication in N -methyl pyrrolidone. Owing to more exposed active sites and shorter migration distances of charge carriers, the photocatalytic hydrogen production rate of the CPP 2-D nanosheets is 1.5–20 times higher than those of their bulk counterparts. The current study represents the first systematic report on the solvent-assisted exfoliation of CPP materials to produce 2D ultrathin lamellae from bulk CPPs with common structures, which might provide new possibilities for the practical application of 2D CPPs.